USE OF GEOSPATIAL TOOLS TO IDENTIFY SOIL RELATED CONSTRAINTS IN MANGO GROWING SOILS OF THE YSR KADAPA DISTRICT OF ANDHRA PRADESH - M.BALAKRISHNA*, T. GIRIDHARA KRISHNA, K.V. NAGAMADHURI, P.SUDHAKAR, B. RAVINDRA REDDY and K.M.YUVARAJ, (The Journal of Research ANGRAU, 2022)
Using a GPS-based survey, the detailed soil fertility status of mango-growing soils in twelvemandals of the YSR Kadapa district (Andhra Pradesh) was explored in 2019-20 to discover soilrelatedcrop production restrictions. pH, EC, OC, and accessible N, P, and K were measured in georeferencedcomposite surface(0-30cm) soil samples. In terms of response, almost all soils were neutralto mildly alkaline. The electrical conductivity (EC) of the soil was within acceptable limits for crops(0.48 dSm-1). The average content of soil organic carbon was 4.2 g kg-1, with a range of 1.3 to 7.2 gkg-1. The accessible soil nitrogen, phosphorus, and potassium were found to be 229.65, 21.28, and264.11 kg ha-1, respectively. Using the ArcGIS programme, thematic soil fertility maps were createdfor each soil parameter to provide ready-to-understand information about soil fertility status and actas a decision-making tool for effective mango production.